Lesson planning in the EFL preservice teachers’ practicum at an Ecuadorian public university during October 2023 - March 2024 semester - Vicente Jiménez, Yoana Paola (2024)
Lesson planning is an integral aspect in the knowledge and training of EFL teachers, providing a framework for effective classroom instruction. Despite its importance, based on the researcher’s experience, preservice teachers present some challenges in lesson plan designing. Based on this context, this research aimed to describe EFL preservice teachers' knowledge on lesson plan designing during their practicum, identifying strengths and weaknesses. For this purpose, the qualitative method and a case study approach were employed, analyzing the lesson plans, field notes, and reflective journals of four preservice teachers who were doing their practicum in the teacher education program at “Universidad Nacional de Loja”. Content analysis was used to evaluate the components of 16 lesson plans through a rubric and field notes. Findings revealed that lesson objectives were clear and aligned with Bloom's Taxonomy, but the ABCD format was not well implemented. Practice activities were designed to reinforce language skills, but in some cases lacked variety. Instructional materials were designed to promote participation. Finally, the assessment tasks showed alignment with the objectives. Consequently, it was concluded that the preservice teachers demonstrated strengths in designing clear objectives, effective practice activities, and interactive instructional materials. However, some of them showed weaknesses in designing objectives that were not aligned with Bloom's Taxonomy, incomplete use of the ABCD format, limited variety in practice activities, instructional materials that lacked alignment with the objectives and in the fulfillment of assessment tasks and planned lessons. Key Words: Lesson planning, EFL preservice teachers, practicum.